SISTEM RELIGI DALAM CERITA RAKYAT NE"™ BARUAKNG KULUB - Willi, Videlia Rika; Seli, Sesilia; Muzammil, Ahmad Rabi'ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe the Dayak Kanayatn people's beliefs about the existence of Jubata, the world of binua, magical things, traditional ceremonies described in the Ne' Baruakng Kulub folklore. This research uses descriptive methods and qualitative research forms. The approach used is a literary sociology approach. The data source is a document in the form of folklore. The folklore used is the Ne' Baruakng Kulub folktale. The technique used is a documentary study technique. The tools used are stationery and laptop. The results of this research show that the religious system in the Ne' Baruakng Kulub folklore includes the Dayak Kanayatn community's belief in Jubata which is reflected through parental advice and pamaliatn prayers. Dayak Kanayatn people believe in the existence of the binua world. The Dayak Kanayatn community's belief in magical things includes prohibitions/amali', sacrificial animals, banyu rice, rasi (natural signs), magical worlds, as well as ghosts and magical creatures. The beliefs of the Dayak Kanayatn community in traditional ceremonies include traditional farming ceremonies, traditional baliatn ceremonies, traditional wedding ceremonies, traditional babalak ceremonies, traditional divorce ceremonies. A lesson plan has been designed using the Ne' Baruakng Kulub folklore as learning material, specifically to achieve KD 3.7 and 4.7 class X SMA.